Long term outcome of laparoscopic liver resection for HCC—is the jury still out? - Seehofer, Daniel; Sucher, Robert (Laparoscopic Surgery, 2018)
After relatively slow implementation in the initial phase, the application of laparoscopic liver resection (LLR) is sharply increasing worldwide within the last years. As for every newly evolving technique, the analysis of long-term outcome and tumor recurrence after LLR is an important issue, before general implementation of this technique. Specifically, in HCC patients, the outcome after liver resection is affected by several factors. The three most important determinants of survival are: (I) severe perioperative complications causing mortality; (II) liver cirrhosis eventually leading to non-tumor related liver failure and deaths; and (III) tumor related factors and the risk of tumor recurrence. Beyond that, also patient age and comorbidities are important cause variables. Especially in evolving techniques, the stage of learning curve and the individual experience of the surgeon are further potential determinants, which need to be considered.